Is there any relationship between plasma antioxidant capacity and lung function in smokers and in patients with chronic obstructive pulmonary disease?. Issue 3 (1st March 2000) - Rahman, Irfan; Swarska, Elzbieta; Henry, Michael; Stolk, Jan; MacNee, William
Abstract : BACKGROUND: It has been suggested that oxidative stress is an important factor in the pathogenesis of chronic obstructive pulmonary disease (COPD). We have shown that an oxidant/antioxidant imbalance occurs in the distal air spaces of smokers and in patients with COPD which is reflected systemically in the plasma. A study was undertaken to determine whether plasma antioxidant status correlated with lung function as assessed by forced expiratory volume in one second (FEV1 ) and forced vital capacity (FVC) in smokers and patients with COPD. METHODS: Plasma antioxidant capacity, assessed by the Trolox equivalent antioxidant capacity (TEAC) as an index of overall systemic oxidative stress, and protein thiol levels were measured in 95 patients with stable COPD, in 82 healthy smokers, and in 37 healthy non-smokers. RESULTS: Mean (SE) plasma TEAC levels were significantly decreased in patients with COPD (0.81 (0.03) mmol/l, p<0.001) and in healthy smokers (0.87 (0.04) mmol/l, p<0.001) compared with healthy non-smokers (1.31 (0.11) mmol/l). The mean differences in plasma antioxidant capacity (mM) were (0.81, 95% confidence interval (CI) 0.22 to 1.48), (0.87, 95% CI 0.2 to 1.46), and (1.31, 95% CI 1.09 to 1.58) in patients with COPD, healthy smokers, and healthy non-smokers, respectively. This reduction was associated with a 29% (95% CI 18 to 38) and a 30% (95% CI 19 to 40) decrease in plasma protein thiol levels in COPD patients and smokers, respectively. Current smoking was not the main contributor to the reduction in antioxidant capacity in patients with COPD as those patients who were still smokers had similar TEAC levels (mean (SE) 0.78 (0.05); n = 25) to those who had stopped smoking (0.84 (0.02); n = 70). No significant correlations were found between spirometric data measured as FEV1 % predicted or FEV1 /FVC % predicted and the plasma levels of TEAC in patients with COPD, healthy smokers, or healthy non-smokers. Similarly, there was no significant correlation between FEV1 % predicted or FEV1 /FVC % predicted and the levels of plasma protein thiols in the three groups. CONCLUSIONS: These data confirm decreased antioxidant capacity in smokers and patients with COPD, indicating the presence of systemic oxidative stress. However, no relationship was found between protein thiols or TEAC levels and measurements of airflow limitation in either smokers or in patients with COPD.